ARIADNE: a scientific navigator to find your way through the resource labyrinth of psychological sciences : tutorial - Hartmann, Helena; Gürsoy, Çağatay; Lischke, Alexander; Mueckstein, Marie; Sperl, Matthias F. J.; Vogel, Susanne; Yang, Yu-Fang; Feld, Gordon Benedikt; Kastrinogiannis, Alexandros; Koppold, Alina (Advances in methods and practices in psychological science, 2025)
Performing high-quality research is a challenging endeavor, especially for early career researchers, in many fields of psychological science. Most research is characterized by experiential learning, which can be time-consuming, error-prone, and frustrating. Although most institutions provide selected resources to help researchers with their projects, these resources are often expensive, spread out, hard to find, and difficult to compare with one another in terms of reliability, validity, usability, and practicability. A comprehensive overview of resources that are useful for researchers in psychological science is missing. To address this issue, we created ARIADNE: a living and interactive resource navigator that helps to use and search a dynamically updated database of resources (https://igor-biodgps.github.io/ARIADNE). In this tutorial, we aim to guide researchers through a standard research project using ARIADNE along the way. The open-access database covers a growing list of resources useful for each step of a research project, from the planning and designing of a study, over the collection and analysis of the data, to the writing and disseminating of the findings. We provide (a) a step-by-step guide on how to perform a research project (in the fields of biological psychology and neuroscience as a case example but with broad application to neighboring fields) and (b) an overview of resources that are useful at different project steps. By explicitly highlighting open-access and open-source resources, we level the playing field for researchers from underprivileged countries or institutions, thereby facilitating open, fair, and reproducible research in the psychological sciences.
Gesehen am 15.10.2025